OVERVALUED EQUITY MEMODERASI PENGARUH KUALITAS AUDIT PADA MANAJEMEN LABA - Luqmanul Hakim; Sudarno Sudarno (Diponegoro Journal of Accounting, 2019)
The objective of this study is to examine the influence of overvalued equity on moderating the relation between audit quality that represented by audit firm size, industry specialization auditor, and audit tenure; in decreasing the act of earning management (discretionary accruals) of all manufacture companies listed in Bursa Efek Indonesia (BEI). This study used secondary data form annual report.The population in this study consists of all listed manufacture firms in Indonesia Stock Exchange in year 2012-2014. Sampling method used is purposive sampling. A total sample of 105 companies were used in analysis. The data is analyzed using multiple linear regression analysis.  The empirical result of this study show that overvalued equity is moderating the relation between audit quality and firm’s discretionary accruals.it is shown by the condition when a firm is overvalued the accruals’ decreasing effect of high quality auditors is reduced.